An Exploratory Study of Resilience in Postsecondary Refugee Students Living in Canada - Wong, Andrew H. C.; Yohani, Sophie (Canadian Journal of Counselling and Psychotherapy, 2016)
Postsecondary refugee students, who may face many challenges in their migration journeys, constitute one refugee population that has been neglected in research. World University Services of Canada annually sponsors refugee students to attend Canadian postsecondary schools. Although students with refugee experiences are expected to face many challenges in postsecondary schools, 85% of them earn a bachelor’s degree. This qualitative case study utilized the ecological-transactional model to understand this refugee population’s resilience. Results suggest that resilience is cultivated by family, resettlement community, and educational supports. These findings inform the need to establish community supports to foster educational success.